Human Body Composition and Immunity: Visceral Adipose Tissue Produces IL-15 and Muscle Strength Inversely Correlates with NK Cell Function in Elderly Humans - Al-Attar, Ahmad; Presnell, Steven R.; Clasey, Jody L.; Long, Douglas E.; Walton, R. Grace; Sexton, Morgan; Starr, Marlene E.; Kern, Philip A.; Peterson, Charlotte A.; Lutz, Charles T. (Frontiers in Immunology, 2018)
Natural killer (NK) lymphocyte-mediated cytotoxicity and cytokine secretion control infections and cancers, but these crucial activities decline with age. NK cell development, homeostasis, and function require IL-15 and its chaperone, IL-15 Receptor alpha (IL-15Rα). Macrophages (Mφ) and dendritic cells (DC) are major sources of these proteins. We had previously postulated that additional IL-15 and IL-15Rα is made by skeletal muscle and adipose tissue. These sources may be important in aging, when IL-15-producing immune cells decline. NK cells circulate through adipose tissue, where they may be exposed to locally-produced IL-15. The objectives of this work were to determine 1) if human muscle, subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) are sources of IL-15 and IL-15 R, and 2) whether any of these tissues correlate with NK cell activity in elderly humans. We first investigated IL-15 and IL-15Rα RNA expression in paired muscle and SAT biopsies from healthy human subjects. Both tissues expressed these transcripts, but IL-15Rα RNA levels were higher in SAT than in skeletal muscle. We also investigated tissue obtained from surgeries, and found that SAT and VAT expressed equivalent amounts of IL-15 and IL-15Rα RNA, respectively. Furthermore, stromal vascular fraction (SVF) cells expressed more IL-15 RNA than did adipocytes. To test if these findings related to circulating IL-15 protein and NK cell function, we tested 50 healthy adults aged >70 years old. Plasma IL-15 levels significantly correlated with abdominal visceral adipose tissue (VAT) mass in the entire cohort and in non-obese subjects. However, plasma IL-15 levels did not correlate with skeletal muscle cross-sectional area and correlated inversely with muscle strength. Plasma IL-15 did correlate with NK cell cytotoxic granule exocytosis and with CCL4 (MIP-1β) production in response to NKp46-crosslinking. Additionally, NK cell responses to K562 leukemia cells correlated inversely with muscle strength. With aging, immune function declines while infections, cancers, and deaths increase. We propose that VAT-derived IL-15 and IL-15Rα is a compensatory NK cell support mechanism in elderly humans.